Microarrays in Diagnostics and Biomarker Development Current and Future Applications - Jordan, Bertrand; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Microarray technology has made strong progress over the past decade, and there have also been significant changes in application areas, from nucleic acids to proteomics and from research to clinical applications. This book provides a comprehensive overview of microarrays in diagnostics and biomarker development, covering DNA, peptide, protein and tissue arrays. The focus is on entities that are in actual clinical use, or quite close, and on recent developments, such as peptide and aptamer arrays. A further topic is the miniaturisation towards “nanoarrays”, which is expected to have great potential in clinical applications. Relevant issues of bioinformatics and statistical analysis of array data are discussed in detail, as well as the barriers to the commercialisation of array-based tests and the vexing IP issues involved. Thus, the book should be very useful tor active array users as well as to newcomers seeking to make the best choice between different technologies.
The microarray paradigm and its various implementations -- DNA arrays in many guises -- Expression profiling for diagnostics -- Genotype characterisation for diagnostics -- Array-CGH and SNP-arrays, the new karyotype -- Protein Microarrays and Their Potential Clinical Applications in the Era of Personalized Medicine -- Peptide arrays -- Slow Off-rate Modified Aptamer (SOMAmer) Arrays for Biomarker Discovery and Diagnostic Applications -- Tissue microarrays for translational research -- Recent and future developments of microarrays:  miniaturization and lab-on-chip approaches -- Analysis of array data and clinical validation of array-based assays -- Challenges in the Commercialization of Array-Based Tests -- Genes, microarrays and patents.
Keywords: Microarrays; Cell biology; Microarrays; Cell Biology